목적 기반 XR 디바이스의 사용성 평가를 위한 평가체계 분석 및 검증 연구 - 차영우; 이기현; 이창기; 권오흥; 이창규; 이주연; 윤정민 (시스템엔지니어링학술지, 2024)
This study aims to compare and evaluate the usability of domestic and overseas XR devices. With the recent release of ‘Apple Vision Pro’, interest in the XR field is increasing rapidly. XR devices are being used in various fields such as defense, medical care, education, and entertainment, but the evaluation system for evaluating usability is still insufficient. Therefore, this study aims to derive improvements in domestic equipment through comparative evaluation of usability for two HMD-type devices and one glasses-type device that are released. In order to conduct the study, 20 participants in their 20s to 30s who were interested in XR devices and had no visual sensory organ-related disabilities were evaluated by wearing VR equipment. As a quantitative evaluation, electromyography through an EMG sensor and the device and body temperature of the device through a thermal imaging camera were measured. As a qualitative evaluation, the safety of wearing, ease of wearing, comfort of wearing, and satisfaction of wearing were evaluated. As a result of comparing the usability of the devices based on the results, it was confirmed that domestic HMD-type device needs improvement in the strap part.
Keywords: XR Devices; Usability Evaluation; ease of wearing; comfort of wearing; HMD-type; glasses-type